ANALISIS KESALAHAN SISWA MTS YANG MEMPUNYAI GAYA BELAJAR VISUAL DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN NEWMAN - Warli; Zilma Ainin Al Ghofiati (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
This study aims to describe the types and causes of errors in grade VII students of MTs Manbail Huda Jenu Tuban who have a visual learning style in solving mathematical problems with flat shapes based on Newman's stages. This type of research is explorative qualitative. The errors studied were based on the criteria in the Newman procedure stage. The main instrument is the researcher, while the supporting instruments are problem solving test sheets, and interview guidelines. The research subjects were seventh grade students of MTs Manbail Huda Jenu Tuban who had a visual learning style. The instrument to determine the visual learning style is a learning style test. The subjects interviewed were selected from students who have a visual learning style by paying attention to the ability to express their thoughts orally and in writing. Three students were interviewed with visual learning styles. The results of the analysis show that the types of errors students who have a visual learning style tend to make errors in processing skills (process skill errors) and writing errors in answers (encoding errors). Factors that cause student errors are because students are not confident in solving problems, forget in the steps or process of working and write the final answer that is not in accordance with the question asked and in a hurry to work and lack of accuracy in solving the problem.